Customer attraction strategies for a SME company in the commercial sector before the Covid-19 [Estrategias de captación de clientes para una Mype del sector comercial ante el Covid-19] - Florián Castillo, Odar Roberto (2022)
The objective of the research was to formulate strategies aimed at attracting clients for a Mype of the commercial sector dedicated to the commercialization of basic food products. The study was prospective. A reliable questionnaire (Cronbach's Alpha of 0.868) and validated by expert judgment was applied to 20 frequent clients sampled for convenience. The main problems encountered were: the lack of use of technologies, the lack of knowledge about strategies and the strong competition that the company faces. Finally, the internal and external analysis strategies were formulated: to provide additional services to clients by frequency of purchase and recommendations; implementation of digital media for advertising and sales, carry out a campaign of low-demand products, recovering the investment or obtaining slight profits; implement resources to avoid contagion in the sale process (seller - customer), implement price or service inquiries through calls or the use of WhatsApp to avoid direct physical contact with customers and possible infections.